Successful intracytoplasmic sperm injection with testicular spermatozoa using pentoxifylline and HOS from a male with necrozoospermia: a case report - Nampalli, Usharani; Fyzullah, Syed; R., Chinmayie; Vijay, Asha Srinivasan; R., Rajsri T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The study was done to compare fertilization, cleavage, and pregnancy outcome of a man affected with necro zoospermia using pentoxifylline and a hypoosmotic swelling (HOS) test to select viable spermatozoa from testicular biopsy specimens. A patient was diagnosed with necrozoospermia by semen analysis, and testicular spermatozoa were injected intracytoplasmically, using pentoxifylline and HOS (Hypo osmotic swelling test) and the following ICSI results were observed. Significantly higher fertilization rates (pentoxifylline 100% vs HOS 80%) were observed. There was no significant difference observed in cleavage rates among both groups. Finally, a healthy female infant with birth weight 3 kg was delivered at the second frozen embryo transfer cycle.it was found that selecting viable spermatozoa using pentoxifylline was more effective in fertilization and pregnancies than obtaining it through a HOS test. ICSI is effective for necrozoospermic man.